GPATCH3 negatively regulates RLR-mediated innate antiviral responses by disrupting the assembly of VISA signalosome - Nie, Ying (PLoS Pathog, 2017)
Upon viral infection, retinoic acid–inducible gene I–like receptors (RLRs) recognize viral RNA and trigger a series of signaling events, leading to the induction of type I interferons (IFNs). These processes are delicately regulated to prevent excessive and harmful immune responses. In this study, we identified G patch domain-containing protein 3 (GPATCH3) as a negative regulator of RLR-mediated antiviral signaling pathways. Overexpression of GPATCH3 impaired RNA virus- triggered induction of downstream antiviral genes, whereas its knockdown had opposite effects and attenuated viral replication. In addition, GPATCH3-deficient cells had higher IFNB1 mRNA level compared with control cells after RNA virus infection. Mechanistically, GPATCH3 was recruited to VISA in a viral infection dependent manner and the assembly of VISA/TRAF6/TBK1 signalosome was impaired in GPATCH3-overexpressing cells. In contrast, upon viral infection, the recruitment of TRAF6 and TBK1 to VISA was enhanced in GPATCH3 deficient cells. Taking together, our findings demonstrate that GPATCH3 interacts with VISA and disrupts the assembly of virus-induced VISA signalosome therefore acts as a negative regulator of RLR-mediated innate antiviral immune responses.